Longitudinal Changes in Cardiac Structure and Function in Pediatric Kidney Transplant Recipients. Issue 8 (2nd June 2022) - de Verteuil, Isabel; Fitzpatrick, Jessica; Alvarez Elias, Ana Catalina; Banh, Tonny; Vasilevska-Ristovska, Jovanka; Browne, Jordan; Bondi, Bianca C.; Hui, Wei; Slorach, Cameron; Wei Teoh, Chia; Langlois, Valerie; Mertens, Luc; et al.
Abstract : Background: Cardiovascular disease results in increased morbidity and mortality in pediatric kidney transplant recipients. Longitudinal changes in cardiac structure and function and the association with blood pressure control over time in pediatric kidney transplant recipients are unknown. Methods: To determine the influence of blood pressure control on cardiac changes following pediatric kidney transplant, we conducted a retrospective cohort study of children who received their first kidney transplant at the Hospital for Sick Children from 2004 to 2015. Children were followed until transfer to adult care or censoring in July 2018. Cardiac structure and function parameters were collected from clinical echocardiograms and assessed using standardized scores. Blood pressure control was determined by systolic blood pressure Z scores (above or below the 90th percentile) in combination with antihypertensive medications. A segmented mixed-effects model assessed Z scores of interventricular septum thickness, left ventricular end-diastolic dimension, and left ventricular posterior wall dimension. Results: Of 142 children included, 58% were men, mean age at transplant was 11 (±4.5) years, and average follow-up time was 4 (±3) years. All cardiac structural Z scores improved during follow-up. Interventricular septum thickness normalized at 4.0 years post-transplant. Left ventricular end-diastolic dimension normalized at 1.5 years post-transplant. Left ventricular posterior wall dimension normalized at 6.3 years post-transplant. Left ventricular mass index showed sustained improvement up to 12 years post-transplant. Individuals with uncontrolled blood pressure had increased left ventricular mass (β=2.97 [95% CI, 0.77–5.16]). Conclusions: Cardiac structural abnormalities improve following kidney transplantation and normalize within 7 years, especially with controlled blood pressure. Strict blood pressure control is critical after pediatric kidney transplantation.